Co-evolution of the branch site and SR proteins in eukaryotes - Plass, Mireya; Agirre, Eneritz; Reyes, Diana; Camara, Francisco; Eyras, Eduardo (Trends in genetics, 2008)
Serine–arginine-rich (SR) proteins are essential for splicing in metazoans but are absent in yeast. By contrast, many fungi have SR protein homologs with variable arginine-rich regions analogous to the arginine–serine-rich (RS) domain in metazoans. The density of RS repeats in these regions correlates with the conservation of the branch site signal, providing evidence for an ancestral origin of SR proteins and indicating that the SR proteins and the branch site co-evolved.